Causes of blindness at the "Wiyata Guna" School for the Blind, Indonesia. Issue 9 (20th August 2003) - Sitorus, R; Preising, M; Lorenz, B
Abstract : Aim: To determine the anatomical site and patterns of cause of blindness in one of the biggest schools for the blind in Indonesia with a view to determining potentially preventable and treatable causes. Methods: 165 students in one school for the blind in Bandung, Indonesia, were examined clinically and data reported using the WHO/PBL childhood blindness assessment form. Results: Most of the students (96.4%) were blind (BL); 3% were severely visually impaired (SVI). The major causes of SVI/BL in this study were: (1) corneal staphyloma, corneal scar, and phthisis bulbi (mainly attributed to infection) in 29.7%; (2) retinal dystrophies (mainly Leber congenital amaurosis, early onset retinitis pigmentosa) in 20.6%; (3) congenital and familial cataract (13.3%); (4) microphthalmus, anophthalmus (10.9%). The whole globe was the major anatomical site of visual loss (32.7%), followed by the retina (26.0%), cornea (17.6%), lens (13.3%), optic nerve (6.1%), and uvea (4.3%). Conclusions: This is a small study in a selected population and the results should be interpreted with caution. This blind school study, adopting the WHO/PBL eye form for data analysing, is the first reported for Indonesia. Hereditary disease and infective causes of blindness are the predominant causes of blindness, accounting for 42.4% and 29.7%, respectively. This pattern of causes is a mixed pattern which lies in an intermediate position between the patterns seen in developing countries and those seen in developed countries. The importance both of preventive public health strategies and of specialist paediatric ophthalmic and optical services in the management of childhood blindness in Indonesia are therefore strongly suggested to cover the problems that exist.